Pengaruh Informasi Produk, Risiko Investasi, Kepuasaan Investor dan Minat Mahasiswa Berinvestasi - Arlin Ferlina Mochamad Trenggana; Riswan Kuswardhana (Jurnal Sekretaris dan Administrasi Bisnis, 2017)
Students become the target of Indonesia Stock Exchange (BEI) and the Financial Services Authority (OJK) because of the age of 17-20 years is still low in investing in stock markets, where one of the programs that is done is by having a gallery of Investment Securities (GIBEI). The purpose of the research was to analyze and review the effect of product information, risk investment and investor satisfaction to interest in investing among the students of the GIBEI members at the Telkom University. This type of research is descriptive and verificative, with 31 students of the GIBEI members at the Telkom University serve as total sampling. Results of the study showed that only informed of products and satisfaction of investor partially significant effect to interest in investing, while simultaneously effect the whole variable (product information, investment risk and the satisfaction investors) to interest in invest is equal to 70.6%. Keywords: Product Information, Investment Risk, Investor Satisfaction, Interest in Investing